¿Suicide, pathology or reasoned decision? - Vargas Rojas, Pablo (2024)
This essay addresses the question of the rationality of suicide, exposing it as a public health problem linked to the existence of mental disorders. It shows the rational weakness in the freedom to decide how and when to die in cases where there is not even a vital commitment. In this way, it reflects the neglect of the causes associated with mental illnesses, whose situation is more critical in vulnerable populations, such as older adults and victims of gender violence